Operation Research and Formation of the Harvesting Transport Complex of the Grain Harvesters of Foreign Production - G. A. Iovlev; A. G. Nesgovorov; I. I. Goldina (Сельскохозяйственные машины и технологии, 2020)
The authors showed that the main condition for assessing the harvesting transport complex is to reduce costs during harvesting and transportation of grain crops.(Research purpose) To assess the technical and economic indicators and operational properties of foreign grain harvesters and their impact on the productivity of the entire harvesting transport complex. Based on the statistical data obtained during the information collection, to calculate the indicators that aff ect the harvesting transport complex management.(Materials and methods) The authors used statistical materials on the combine harvesters operation, transport vehicles for transportation. They took studied combine harvesters and vehicles technical characteristics. They considered the elements of the theory of probability for the formation of the harvesting transport complex. The studies were carried out simultaneously in two structural divisions of an agricultural organization, located at a distance of 19-20 kilometers from each other. Economic and statistical, forecasting, economic and mathematical modeling, expert assessments and others methods were used.(Results and discussion) The authors received 89 values for the indicator "Time to fi ll the combine harvester bunker", 45 – according to the criterion "Waiting time for vehicle loading". They calculated the mathematical expectation of the fi rst indicator: in the fi rst harvesting team for the Tucano 450 – 22.68 minutes; Mega 370 – 20.74 minutes; for a Tucano 450 from the second harvesting team – 19.24 minutes.(Conclusions) The authors revealed the features of harvesting transport complexes formation, consisting of foreign combine harvesters and vehicles. They determined the productivity, quality indicators of the technological process of threshing grain crops and yield, at which the use of foreign combine harvesters became economically feasible.